Employability related factors of gastronomy university school graduates in Lima, Peru - Uribe Hernández, Yrene Cecilia (2019)
The objective of the research was to identify the main perception indicators on citizen security in the Magdalena del Mar district. 224 people 18 years of age and older were surveyed. A descriptive statistic was carried out with confidence intervals to estimate the population proportions of the variable under study “perception”. As a relevant conclusion, it was identified that the main cause of citizen insecurity in the Magdalena del Mar district is robbery.The inhabitants ask for more social organization to feel more secure in the district. The inhabitants qualify as regulating the efficiency of the police in the presence of different acts of citizen security. More than half of the respondents think that the situation on citizen security in